2003
DOI: 10.1080/07448480309595734
|View full text |Cite
|
Sign up to set email alerts
|

Differences in African American and White College Students' Drinking Behaviors: Consequences, Harm Reduction Strategies, and Health Information Sources

Abstract: The authors explored the differences between African American and White college students' drinking behaviors and their attitudes toward consequences, harm-reduction strategies, and health information sources. They collected data from a randomly selected sample of 1,110 students in a large public university to examine the effects of a high-risk drinking prevention intervention. In the current analysis, they compared African American and White students on indicators of high-risk drinking, drinking consequences, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 3 publications
4
28
2
Order By: Relevance
“…Racial differences had also been reported, as White students tended to drink more than their non-White counterparts (Wechsler et al, 2003), and African American students reported fewer negative consequences from drinking than Whites (Siebert, Wilke, Delva, Smith, & Howell, 2003). These racial differences in alcohol consumption had also been found in an all female sample (Madison-Colmore, Ford, Cooke, & Ellis, 2003).…”
Section: Demographic Factorsmentioning
confidence: 82%
“…Racial differences had also been reported, as White students tended to drink more than their non-White counterparts (Wechsler et al, 2003), and African American students reported fewer negative consequences from drinking than Whites (Siebert, Wilke, Delva, Smith, & Howell, 2003). These racial differences in alcohol consumption had also been found in an all female sample (Madison-Colmore, Ford, Cooke, & Ellis, 2003).…”
Section: Demographic Factorsmentioning
confidence: 82%
“…Though the link between alcohol and sexual assault has long been studied, few have studied how race, alcohol related sexual assault, and prevention programming intersect. One reason these are important phenomena to study together is that racial groups differ in their consumption of alcohol, with greater consumption of alcohol reported by Caucasians than African Americans and Asian college students (Luczak et al 2001;Mohler-Kuo et al 2004;Siebert et al 2003). These different norms for drinking between the various races may significantly impact the context in which rape occurs on college campuses.…”
mentioning
confidence: 93%
“…Although African American students drink relatively less than their European American peers, excessive use and problems are still prevalent among this group (Meilman et al, 1995;Siebert et al, 2003). Furthermore, African American students report frequent experiences with discrimination (Chao et al, 2012;Swim et al, 2003).…”
Section: Frican Americans Compared With Europeanmentioning
confidence: 99%